NALISIS BIAYA PROYEK DENGAN METODE EARNED VALUE DALAM PROSES KINERJA (Studi Kasus Pada Proyek Pembangunan Universitas Katholik Widya Mandala Pakuwon Citi-Surabaya) - Witjaksana, Budi; Reresi, Samuel Petrik (Universitas 17 Agustus 1945 Surabaya, 2012)
Nowadays construction projects grow bigger and more complicated both of physical aspects and costaspects, so it takes a project management from the initial phase to project completion phase. In each project.control measure is required in terms of cost and time. The earned value method combines elements ofschedule, cost, and job performance. Earned value analysis will be applied to development projects ofCatholic University Widya Mandala Pakuwon City Surabaya. The purpose of finding out its performance ismonitoring and controlling the project, so that when there is any deviation, certain action can be taken soon. This research based on the weekly report of the project work continuously for more than 11 (eleven) months.The advantage of this method is it’s able to describe the relationship between progresses with the allocatedbudget. Based on the analysis result on each review, the performance of the project will be known everyweek. Where at the end of the review, the project experienced schedule posponement. From the calculationresult that has been done, the project cost of the remaining work at the 42 weeks is Rp. 6.241.228.702,00 andthe total cost of the project at 42 weeks is Rp.10.864.777.052,29. It is recommended that in the research, datacollection process about direct costs and indirect costs must be surveyed in detail.Keywords : earned value, cost